2021
DOI: 10.1002/acp.3808
|View full text |Cite
|
Sign up to set email alerts
|

“What works?” Systematic reviews and meta‐analyses of the investigative interviewing research literature

Abstract: While the practice of investigative interviewing has traditionally been grounded in customary knowledge, decades of research have now enhanced our understanding of the limits of these practices and led to the development of novel, theoretically informed approaches. The maturity of any science is likely best evidenced in the conduct of systematic reviews and meta‐analyses, and the investigative interviewing research literature has reached just such a period in its development. This paper reviews current “best p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…As such, referring to such kind of studies is much better for the conceptualization of language teaching and learning. The systematic review in the current paper adhered to a precise scheme examined research according to clearly identified principles and adopted an all-inclusive investigation approach (Gough, Oliver, & Thomas, 2012;Meissner, 2021). To define and choose the journals to be included in the review, the following parameters were settled:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, referring to such kind of studies is much better for the conceptualization of language teaching and learning. The systematic review in the current paper adhered to a precise scheme examined research according to clearly identified principles and adopted an all-inclusive investigation approach (Gough, Oliver, & Thomas, 2012;Meissner, 2021). To define and choose the journals to be included in the review, the following parameters were settled:…”
Section: Methodsmentioning
confidence: 99%
“…As Petticrew and Roberts (2006) stress, principled reviews necessitate researchers to formulate a strategic plan and determine the anteriority of how to single out the research. At that point, it is decisive to specify studies, discover relevant databases so as to retrieve the research and shape their data gathering system (Meissner, 2021). Therefore, after scrutinizing the relevant literature, the inclusion criteria for the current study were set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on interviewing suspects has become more focused on understanding how to retrieve reliable information from suspects (Vrij, 2008). Studies on the relationship between (categories of) interview techniques and retrieving information show that rapport building and (ways of) confronting could significantly influence a suspects' willingness to disclose information (Alison et al, 2013;Bull, 2014Bull, , 2019Granhag & Hartwig, 2015;Kelly et al, 2013;Meissner, 2021).…”
Section: Interview Techniquesmentioning
confidence: 99%
“…Although, in the past decades, research on interviewing suspects has grown steadily worldwide, interviewing high-status suspects has received little attention. Most of the studies on interviewing suspects, using methodologies such as laboratory experiments, in-depth interviews or recordings of actual investigative interviews, focus primarily on the interviewing practices of the police or on human intelligence interviewing in a military context (Meissner, 2021;Miller et al, 2018;Vrij & Granhag, 2014). Only a few studies have focused on fraud suspects such as the suspects of social security benefit fraud (Walsh & Bull, 2010, 2012a, 2012b or customs fraud (Granhag et al, 2014).…”
Section: Introductionmentioning
confidence: 99%